Implementasi Nilai-Nilai Jihad dalam Kepemimpinan Pendidikan - Rudi Fahrudin; Agus Herdianto; Syamel Massa Kaulika; Zahra Zahra (El-Idare, 2020)
Jihad is a sensitive term especially for those who quite like the existence of Islam and its teachings due to limited knowledge. In fact, the term jihad has broad meaning, but it is often interpreted narrowly as war. The principal can play a major role in turning the connotation of jihad into beauty. To begin to change the connotation it needs to start from practicing the value of jihad in his profession. The principal is the engine driving an educational institution and the resources within it. To the teacher and staff, also to students or students.This discussion aims to explore the context of jihad which is implemented in the principal's leadership style. Data mining is done by library research. The results show that jihad can be implemented in the principal's leadership style which is a sincere and total performance. Jihad that leads to war is textual understanding what is used is the context of jihad which is the spirit of renewal. In the future, the term jihad should be understood in depth and provide information about true jihad without lies.